The Impact of Industrialised Building System (IBS) On Local Labour - Lui, Jing Wen (2020)
As the emerging of technology, the construction industry of Malaysia undergoes a transformation from the conventional construction into advanced and mechanised approach, namely Industrialised Building System (IBS). IBS is an innovative construction technique that emphasizes on prefabrication of building components with the application of automation and robotics to tackle the issues of high dependency on foreign labours. The main setbacks of implementing the automation and robotics in IBS is that local labours will be impacted. In this research, the barriers and impacts of IBS on the local labours were investigated. In-depth interview sessions had been conducted on the contractors who experienced in conventional and IBS project. The result showed that the implementation of IBS has reduced the number of labours required on-site but local labours are maintained. Local labours are maintained in working with the technical team in IBS projects. Alternative initiatives are currently implementing by the government and authorities to retrain and reskill the local labours in order to stabilise their employment in construction project.